2023
DOI: 10.18176/jiaci.0851
|View full text |Cite
|
Sign up to set email alerts
|

Very Rapid Improvement in Extended Nitric Oxide Parameters Is Associated With Clinical and Functional Improvement in Patients With Chronic Rhinosinusitis With Nasal Polyps Treated With Dupilumab

Abstract: Background: Dupilumab, an anti-IL-4 receptor alpha monoclonal antibody, has been recently approved for the treatment of chronic rhinosinusitis with nasal polyps (CRSwNP) and moderate to severe asthma, demonstrating a rapid onset of clinical effects. CRSwNP is characterized by an extended type-2 inflammatory involvement that can be assessed by extended nitric oxide analysis. Objective: In this study we investigated whether Dupilumab is associated with a rapid improvement in extended nitric oxide parameters, lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…FeNO in CRS so far has focused on predicting the presence of occult asthma (331)(332)(333) , as well as tracking improvement in asthma after treatment of CRS (334,335) . Nasal nitric oxide (nNO) has been described as a marker of and outcome measure for eosinophilic or type-2 CRS that can improve with treatment of CRS (335) but its measurement is confounded by physical obstruction of sinus ostia.…”
Section: Fraction Exhaled Nitric Oxide (Feno)mentioning
confidence: 99%
See 1 more Smart Citation
“…FeNO in CRS so far has focused on predicting the presence of occult asthma (331)(332)(333) , as well as tracking improvement in asthma after treatment of CRS (334,335) . Nasal nitric oxide (nNO) has been described as a marker of and outcome measure for eosinophilic or type-2 CRS that can improve with treatment of CRS (335) but its measurement is confounded by physical obstruction of sinus ostia.…”
Section: Fraction Exhaled Nitric Oxide (Feno)mentioning
confidence: 99%
“…FeNO in CRS so far has focused on predicting the presence of occult asthma (331)(332)(333) , as well as tracking improvement in asthma after treatment of CRS (334,335) . Nasal nitric oxide (nNO) has been described as a marker of and outcome measure for eosinophilic or type-2 CRS that can improve with treatment of CRS (335) but its measurement is confounded by physical obstruction of sinus ostia. For example, despite the higher prevalence of type-2 inflammation, CRSwNP is associated with lower nNO levels compared to CRSsNP or control patients (336) and ESS can increase nasal FeNO due to enlarged sinus ostia, despite the lack of obvious mucosal inflammation (337,338) .…”
Section: Fraction Exhaled Nitric Oxide (Feno)mentioning
confidence: 99%
“…Nevertheless, nNO normalization has been demonstrated after both medical and surgical opening of sinonasal ostia, thus providing evidence of its possible application as a marker of treatment response [104]. Moreover, Paoletti et al demonstrated the effectiveness of anti-IL-4 receptor alpha monoclonal antibody (dupilumab), proving a rapid improvement in nNO values and other markers of disease severity as early as 15 days after the initiation of treatment [105].…”
Section: Nitric Oxide: a Systemic Mediatormentioning
confidence: 99%
“…Additionally, dupilumab, an anti-IL-4 receptor alpha monoclonal antibody, has been used recently in the treatment of CRSwNP. Patients with CRSwNP treated with dupilumab were evaluated through extended nitric oxide analyses (exhaled, FENO; bronchial, JawNO; alveolar, CalvNO components; nasal, nNO) where the results showed that nitric oxide significantly improved after 15 days of treatment [21].…”
Section: Chronic Rhinosinusitis (Crs) and Nasal Polyps (Np)mentioning
confidence: 99%